Donnelie (Warwicks) – identifying a lost Domesday manor and understanding the nature and function of its haia (hay). (2nd January 2017) - Bassett, Steven; Wager, Sarah
Abstract : The hitherto lost Domesday manor of Donnelie (Warwicks), which had a haia (hay), is likely to have lain in the ecclesiastical parish of Wootton Wawen and been absorbed into the manor of Wootton by the end of the twelfth century. The location of Wootton's late medieval hay (presumably once Donnelie's ) is identified, and is found to be unsuitable for the commonly accepted purpose of hays, the taking and holding of deer. A brief discussion of the role of medieval hays points to a previously unrecognized type which existed independently of woodland – a fenced enclosure for holding domestic livestock, which in some cases may have been a gathering point for animals being taken to be sold or exchanged.